Older adults' perspectives towards optimizing lifestyle behaviors and strategies to support healthy brain ageing during COVID-19 restrictions - Joyce Siette; Joyce Siette; Laura Dodds; Cristy Brooks; Kay Deckers (Frontiers Media S.A., 2023)
IntroductionIt is unknown how the impact of COVID-19 restrictions has affected brain healthy behaviors that contribute to dementia risk reduction in older adults. Our aim was to explore perspectives of older adults on lifestyle behaviors that support positive brain health and dementia risk reduction during and following COVID-19 restrictions.MethodsCommunity-dwelling older Australians (N = 159) during June to October 2021 (the second wave of COVID-19 restrictions) who had taken part in a pre-post dementia risk reduction intervention program were invited to discuss the impact of COVID-19 on their lifestyle behaviors. Semi-structured interviews explored individual's adaptability to pandemic restrictions, intended behavior changes following restrictions easing, and feedback on the effectiveness of ongoing intervention programs for sustaining brain health. Thematic data analysis was performed using a deductive approach.ResultsParticipants had an average age of 73.1 years (SD = 5.6; range: 65-90), majority were female (74.7%), lived in a major city (82.2%) and mean 9.5 years (SD = 1.7) of education. Older adults' views about lifestyle prevention strategies during the pandemic were both positive (e.g., more spare time and adaptive leisure activities) and negative (e.g., social isolation, lack of motivation, adverse emotions). Participants highlighted a continuous conscious effort to adapt certain brain healthy behaviors despite the persistence of adverse impacts of COVID-19 restrictions. Participants also expressed the intention and desire to revert to their previous lifestyle before the COVID-19 pandemic or a sense of the 'new normal'.ConclusionThis formative research will inform future interventions targeting dementia risk reduction to consider the immediate and lasting effects of COVID-19 restrictions on older adult's lifestyle behavior.